Pertussis in Southeast Asia: country-level burden and recommendations from the Global Pertussis Initiative - Nguyen The Nguyen, Phung (2024)
The Global Pertussis Initiative (GPI) met in March 2024 to discuss the burden of pertussis and prevention efforts in six Southeast Asian countries: Cambodia, Indonesia, Malaysia, Singapore, Thailand, and Vietnam. Except for Cambodia, pertussis is a notifiable disease; data accuracy varies within and between countries. Most cases in the region are diagnosed based on clinical suspicion. Whole-cell and acellular pertussis combination vaccines are available, but the composition differs between countries. Immunization against pertussis is well-established, but policies regarding boosting vary. Vaccination in pregnancy (ViP) represents a still-neglected opportunity to protect infants. The GPI recommends enacting ViP in countries without and increasing coverage in countries with policies already in place. There is a need to correct the misperception that pertussis affects children exclusively and that childhood vaccines provide lifelong protection. Education is key to widespread understanding of the threat of pertussis and to removing barriers to vaccination in Southeast Asia.